ЗАЛУУЧУУДЫН ТАЛААР БАРИМТЛАХ ТӨРИЙН БОДЛОГОД ХИЙСЭН БОДЛОГЫН ШИНЖИЛГЭЭ - С.Мөнхбат; Б.БАТ-ЭРДЭНЭ (Politology, 2023)
So many countries processed and implemented of the state policy on youth in the world. Because, the youth are the future of every nation. Therefore, any state policy has been active for many young people. These, to belong economic, social, education, health and political participation policy. In this research article, we have analysis the Mongolian government’s economic and social policy for youth people and its implementation.